RANGKUMAN dan pengayaan bahasa Inggris kelas IV SD semester 1 /Emilya Tyas W.N, dkk ; editor, Maria Agustina S, Flora Maharani ; ilustrator, Hernawan - Emilya Tyas W.N; Maria Agustina S; Flora Maharani; Hernawan (Kanisius, 2016)
75 hlm. : ilus. ; 25 cm.